Analisis Kompetitif Pegadaian Syariah Purwokerto Menggunakan Metode Porter’s Five Forces Strategi Pemasaran Produk Gadai Tabungan Emas - Rizka Sobriyani Pratiwi; Dianatul Aizza; Dimas Saputro; Yoiz Shofwa Shafrani (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the competitive strength of Pegadaian Syariah Purwokerto using Porter’s Five Forces method and evaluate the marketing strategy for its Gadai Tabungan Emas product. In the digital era with increasing competition, understanding the external forces affecting the industry is crucial for formulating an effective strategy. The analysis shows that Pegadaian Syariah Purwokerto faces high threats from new entrants and substitute products, as well as high bargaining power of buyers. However, Pegadaian Syariah can leverage its internal strengths, such as a strong corporate image and public trust, to maintain its competitive position. Product differentiation, focusing on local syariah market segments, and service digitalization are key to improving its competitive position. The study provides recommendations for Pegadaian Syariah Purwokerto’s management to aggressively adopt technology and strengthen syariah-based educational marketing